FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT PARTISIPASI IBU BALITA DALAM KEGIATAN POSYANDU DI DESA TAMBANG KECAMATAN TAMBANG KABUPATEN KAMPAR RIAU - Mita Permata Dwi; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research is titled "Factors related to the participation rate of toddler mothers in Posyandu activities at the mining village in Kampar Riau Regency". This research aims to determine the level of participation of toddler mothers in Posyandu activities and factors related to the participation rate of toddler mothers in Posyandu activities in the mining village sub-district of Kampar Riau. The method used in this research is quantitative research method with cross sectional study design. The population in this study is the mother who has a toddler in the village mining district of Kampar district mines, and a large sample of 52 toddler mothers. The variables in this study are the participation rate of toddler mothers in Posyandu activities, maternal level of toddlers, Mother's level of knowledge, working status of toddler mothers, the residence distance of toddler mothers, and family support. Data is analyzed with product momment correlation. Based on the results of the study, the level of participation of the toddler mother in posyandu activities in the mining village sub-district in Posyandu activities in the category of "low" is 57.7% while the "high" category is only 19.2%, and Factors related to the participation rate of toddler mothers in Posyandu activities in the mining village in the district of Kampar District mines in order of the family support with R value of 0.643, the level of knowledge of the toddler mother with the value R of 0.641, the level of maternal education of toddlers with R value of 0.478, residence distance with R value of 0.404, as for the working status is not related to participation rate with R value of-0.046 Keywords: Participation, Posyandu, Toddler Mother